Pengaruh Social Support, Innovative Work Behavior, Worklife Balance, dan Organizational Commitment Terhadap Job Performance Karyawan Pada Gerai Bubble Tea di Mall Jakarta Barat - Chairunisah, Nabillah; Tsabitah, Dinah Amira; Emilisa, Netania; Kurniawan, Aziza Idris (Peneliti.net, 2023)
This study aims to examine and analyze the variables social support, innovative work behavior, worklife balance,and organizational commitment that have a positive effect on job performance among bubble tea consumers at the West Jakarta mall. The sample used in this study amounted to 135 respondents. The sampling technique used was purposive sampling. Data were analyzed using the Structure Equation Model (SEM) method. The results of this study are: (1) Social support has a positive effect to Job Performance, (2) Innovative work behavior has a positive effect to Job Performance, (3) Worklife balance has a positive effect to Job Performance, and (4) Organizational Commitment has a positive effect to Job Performance.